Spatial structure in Neptune’s 7.90-m stratospheric CH emission, as measured by VLT-VISIR - Sinclair, JA; Orton, GS; Fletcher, LN; Roman, M; de Pater, I; Encrenaz, T; Hammel, HB; Giles, RS; Velusamy, T; Moses, JI; Irwin, PG; Momary, TW; et al. (Elsevier, 2020)
We present a comparison of VLT-VISIR images and Keck-NIRC2 images of Neptune, which highlight the coupling between its troposphere and stratosphere. VLT-VISIR images were obtained on September 16th 2008 (UT) at 7.90 μm and 12.27 μm, which are primarily sensitive to 1-mbar CH4 and C2H6 emission, respectively. NIRC2 images in the H band were obtained on October 5th, 6th and 9th 2008 (UT) and sense clouds and haze in the upper troposphere and lower stratosphere (from approximately 600 to 20 mbar). At 7.90 μm, we observe enhancements of CH4 emission in latitude bands centered at approximately 25∘S and 48∘S (planetocentric). Within these zonal bands, tentative detections (<2σ) of discrete hotspots of CH4 emission are also evident at 24∘S, 181∘W and 42∘S, 170∘W. The longitudinal-mean enhancements in the CH4 emission are also latitudinally-coincident with bands of bright (presumably CH4 ice) clouds in the upper troposphere and lower stratosphere evidenced in the H-band images. This suggests the Neptunian troposphere and stratosphere are coupled in these specific regions. This could be in the form of (1) ‘overshoot’ of strong, upwelling plumes and advection of CH4 ice into the lower stratosphere, which subsequently sublimates into CH4 gas and/or (2) generation of waves by plumes impinging from the tropopause below, which impart their energy and heat the lower stratosphere. We favor the former process since there is no evidence of similar smaller-scale morphology in the C2H6 emission, which probes a similar atmospheric level. However, we cannot exclude temperature variations as the source of the morphology observed in CH4 emission. Future, near-infrared imaging of Neptune performed near-simultaneously with future mid-infrared spectral observations of Neptune by the James Webb Space Telescope would allow the coupling of Neptune's troposphere and stratosphere to be confirmed and studied in greater detail.